The phase shift between potential and kinetic energy in human walking - Cavagna, G. A.; Legramandi, M. A. (Journal of Experimental Biology, 2020)
It is known that mechanical work to sustain walking is reduced, owing to a transfer of gravitational potential energy into kinetic energy, as in a pendulum. The factors affecting this transfer are unclear. In particular, the phase relationship between potential and kinetic energy curves of the center of mass is not known. In this study, we measured this relationship. The normalized time intervals a, between the maximum kinetic energy in the sagittal plane (Ek) and the minimum gravitational potential energy (Ep), and ß, between the minimum Ek and the maximum Ep, were measured during walking at various speeds (0.5-2.5 m s-1). In our group of subjects, a=ß at 1.6 m s-1, indicating that, at this speed, the time difference between Ep and Ek extremes is the same at the top and the bottom of the trajectory of the center of mass. It turns out that, at the same speed, the work done to lift the center of mass equals the work to accelerate it forwards, the Ep-Ek energy transfer approaches a maximum and the mass-specific external work per unit distance approaches a minimum.